Flow cytogenetics and plant genome mapping - Dolezel, Jaroslav; Kubaláková, Marie; Bartos, Jan; Macas, Jirí (Chromosome research, 2004)
The application of flow cytometry and sorting (flow cytogenetics) to plant chromosomes did not begin until the mid-1980s, having been delayed by difficulties in preparation of suspensions of intact chromosomes and discrimination of individual chromosome types. These problems have been overcome during the last ten years. So far, chromosome analysis and sorting has been reported in 17 species, including major legume and cereal crops. While chromosome classification by flow cytometry (flow karyotyping) may be used for quantitative detection of structural and numerical chromosome changes, chromosomes purified by flow sorting were found to be invaluable in a broad range of applications. These included physical mapping using PCR, high-resolution cytogenetic mapping using FISH and PRINS, production of recombinant DNA libraries, targeted isolation of markers, and protein analysis. A great potential is foreseen for the use of sorted chromosomes for construction of chromosome and chromosome-arm-specific BAC libraries, targeted isolation of low-copy (genic) sequences, high-throughput physical mapping of ESTs and other DNA sequences by hybridization to DNA arrays, and global characterization of chromosomal proteins using approaches of proteomics. This paper provides a comprehensive review of the methodology and application of flow cytogenetics, and assesses its potential for plant genome analysis.
Keywords: translokace genetická; Translocation, Genetic; rostliny; karyotypizace; Karyotyping; Physical Chromosome Mapping; chromozomy rostlin; Plants; fyzikální mapování chromozomů; průtoková cytometrie; Chromosomes, Plant; Genome, Plant; Flow Cytometry; genom rostlinný